2021
DOI: 10.1038/s41598-021-90226-2
|View full text |Cite
|
Sign up to set email alerts
|

Refinement of 16S rRNA gene analysis for low biomass biospecimens

Abstract: High-throughput phylogenetic 16S rRNA gene analysis has permitted to thoroughly delve into microbial community complexity and to understand host-microbiota interactions in health and disease. The analysis comprises sample collection and storage, genomic DNA extraction, 16S rRNA gene amplification, high-throughput amplicon sequencing and bioinformatic analysis. Low biomass microbiota samples (e.g. biopsies, tissue swabs and lavages) are receiving increasing attention, but optimal standardization for analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Variable feature counts also suggest differential abundance in sample biomass that can significantly affect alpha and beta-diversity analysis. 70 A proposed methodology to standardize the concentration of samples has been documented by Doan and colleagues. 18 A limitation to our methodology was not performing quantitative polymerase chain reaction (qPCR) to control for sample concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Variable feature counts also suggest differential abundance in sample biomass that can significantly affect alpha and beta-diversity analysis. 70 A proposed methodology to standardize the concentration of samples has been documented by Doan and colleagues. 18 A limitation to our methodology was not performing quantitative polymerase chain reaction (qPCR) to control for sample concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, sample collection strategies may need to be optimized specifically for these low biomass samples; fortunately, recommendations exist [ 45 ] . Previous research has shown that larger volumes of low-biomass samples don’t necessarily lead to significantly increased DNA biomass [ 46 ], and therefore future efforts may yield more success by focusing on improved extraction methods [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore we focused on 16S rRNA gene sequencing data. 16S rRNA gene sequencing is a well-characterized way of detecting and classifying bacterial communities within biological samples (158160), and it is potentially sensitive enough to detect the typically low number of 16S rRNA bacterial gene copies hypothesized to be in the placenta (34, 161). 33 of the 41 studies which implemented 16S rRNA gene sequencing included at least one placental sample from an uncomplicated delivery at term (27-29, 36-45, 47, 49-65, 86, 142).…”
Section: Methodsmentioning
confidence: 99%